Forage demonstration report in Kilimanjaro and Tanga regions, Tanzania - Ngunga, David; Mwendia, Solomon W. (Bioversity International and the International Center for Tropical Agriculture, 2021)
The International Center for Tropical Agriculture (CIAT) implemented Irrigated forage production and environmental interventions in Kilimanjaro and Tanga Regions of Tanzania. Four Districts (Siha, Hai in Kilimanjaro, Muheza and Mkinga in Tanga) were the main activity sites located for establishment of improved irrigated forage demo plots, where Brachiaria hybrid cv Cobra variety and Brachiaria hybrid cv Cayman varieties were introduced in the domo plots. In this work we met two different groups of service providers in the livestock sector in these two Regions.